Contribuição clínica da porosidade cortical na investigação de fragilidade óssea através de hr-pct - Silva, André Mauricio Rique da (2019)
The purpose of this study is to evaluate cortical porosity by high resolution peripheral quantitative microtomography in patients with Cushing’s syndrome, which is characterized by excess production of glucocorticoids by the adrenal glands and their release into the circulation. For this evaluation we used patients aged 29 to 72 years with Cushing’s syndrome (N = 18) and also patients who were part of a control group (N = 23) that make up the HR-pQCT database, or that is, without any bone disease. The procedure was the standard measure for patients from 37 to 82 years old who did not have fractures in their lower and upper limbs. The results showed that the amount of pores in the cortical bone for patients with the aforementioned pathology does not increase in significant proportions, however there was an increase in pore diameter and a decrease in the transition between cortical and trabecular bone. This increase in pore diameter weakens the bones so that peripheral and lower limb fractures can occur. Cushing’s syndrome may have a direct relationship with this increase in diameter, as well as an increase in cortical porosity, when compared to healthy patients in the same age range.